1971
DOI: 10.1136/ard.30.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Review of the results of excision of the metatarsal heads in patients with rheumatoid arthritis.

Abstract: In one set of experiments the harvesting was done on the 5th day and in the other on the 6th day. Might this not account for wide variation in the uptake of thymidine? DR. DAVEY In the first group of experiments we did not find any marked difference in the results, whether cultures were harvested at day 5 or day 6, but this is clearly very late in lymphocyte culture time and there tended to be a fairly wide variation. It is late even for antigen stimulation, and I think that in some of the cultures the pH had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Apart from the one patient (2%) who developed deformity in a fifth toe which had not been operated on, no patient required reoperation on the forefoot after multiple toe procedures. This contrasts with studies of metatarsal head excision techniques in which reoperation rates of 8–36% are quoted [15–35], including series in which first metatarsophalangeal arthrodesis has been performed [17, 30].…”
Section: Discussionmentioning
confidence: 92%
“…Apart from the one patient (2%) who developed deformity in a fifth toe which had not been operated on, no patient required reoperation on the forefoot after multiple toe procedures. This contrasts with studies of metatarsal head excision techniques in which reoperation rates of 8–36% are quoted [15–35], including series in which first metatarsophalangeal arthrodesis has been performed [17, 30].…”
Section: Discussionmentioning
confidence: 92%
“…The main risk of harm reported was infection, which was specifically reported in 8 surgical observational studies (29,31,32,35,39,40,42,43); the frequency of infection in these reports averaged 7.5% (range 1.4 -16%). Individual reports also described delayed wound healing (31,35), skin necrosis (41), and implant fragmentation (31).…”
mentioning
confidence: 97%
“…Improvements in walking ability ranged from 67% to 80% in the remaining 4 studies (36,40). Footwear improvement was noted in 25% of patients (36) and ordinary shoe wear was possible in 45-80% (40,41) of patients postoperatively.…”
mentioning
confidence: 99%
“…Several methods of treating the hallux valgus deformity in RA have been reported, including arthrodesis, joint resection, and arthroplasty with implant for the MTP joint. Good results have been observed in previous surgical procedures [4][5][6][7][8][9][10]. However, a number of authors have found a significant rate of recurrent symptomatic deformities of both the hallux valgus and lesser toes [8,10,11] over time when the hallux valgus deformity is managed by resection-type arthroplasty of the MTP joint.…”
Section: Introductionmentioning
confidence: 76%